Generalized approach to Hurst exponent estimating by time series - Kirichenko, L.; Radivilova, T.; Bulakh, V. (My University, 2018)
This paper presents a generalized approach to the fractal analysis of self-similar random processes by short time series. Several stages of the fractal analysis are proposed. Preliminary time series analysis includes the removal of short-term dependence, the identification of true long-term dependence and hypothesis test on the existence of a self-similarity property. Methods of unbiased interval estimation of the Hurst exponent in cases of stationary and non-stationary time series are discussed. Methods of estimate refinement are proposed. This approach is applicable to the study of self-similar time series of different nature.
Keywords: fractal analysis; short time series; Hurst exponen